IMPACT OF WEST AFRICAN SOY LIMITED (WASIL) ON MAIZE FARMERS FOOD SECURITY IN NORTH-WEST, NIGERIA - Ebenehi, O.; Muntakka, M.; Fawole, B.F. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
In Nigeria, farmers depend largely on supports for farm inputs which can be in the form of subsidies in order to improve their livelihoods. These supports are usually made available and accessible to them by government and non-governmental organizations. In this article, the impact of West African Soy Limited Maize Farmers Intervention Scheme was investigated. The study employed Propensity Score Matching to net out the average treatment effect on treated which is the impact of the programme on the beneficiaries using food security as an outcome indicator. Two hundred and eighty-two (282) households head who benefitted from the programme were purposively and proportionately selected while another Two hundred and eighty-two (282) non-beneficiary’s household heads were randomly selected and used as control group. The result revealed that the programme had a positive and significant influence at 5% level of confidence on their food security status and the average treatment effect on treated (ATT) was 0.2037 (20%). The size of the estimated treatment effect suggests an improvement in the livelihood of the beneficiaries compared to the non-beneficiaries. The programme, though a private sector initiative is such that has potential of ensuring increased income as well as food security of the poor resource small scale farmers in the rural areas of North West, Nigeria. The study therefore recommends that female household head need to be encouraged to key into the programme in order to improve their income base. In addition, there is need for increased and rigorous capacity building of the farmers by extension agents of the programme in order to sustain the gains.